Unity in Diversity - K. Luisa Gandolfo (International Institute of Islamic Thought, 2008)
The field of conflict resolution has rarely been tested so frequently as in the Middle East. Since 1948, internecine conflict has flared in Israel/Palestine, Lebanon, and Iraq, with neighboring states sustaining the consequences of the tensions.Applying interfaith dialogue (IFD) as ameans to promote peaceful relations is thus, by its very nature, fraught with controversy and uncertainty. Yet this unique approach draws on peace-building mechanisms that bear such religious nuances as reconciliation, mercy, and forgiveness. By eschewing secular concepts for religious resources, IFD provides a point from which individuals can transcend the religious divide in search of further understanding and peace.Accordingly, following the activities of IFD organizations in Israel/Palestine, Jordan, Egypt, and Lebanon is a complex undertaking for the authors of Unity in Diversity. Having previously addressed Nonviolence and Peacebuilding in Islam: Theory and Practice (University Press of Florida: 2003) and Dialogue, Conflict Resolution, and Change: Arab-Jewish Encounters in Israel (State University of New York Press: 1999), Abu-Nimer, an associate professor with the International Peace and Conflict Resolution Program, lends a revealing insight into faith-based resolution. Alongside Khoury and Welty, this book introduces IDF and analyzes its application, limitations, and recommendations. Opening with an overview of the “Potentials and Challenges in Interfaith Dialogue in the Middle East” in chapter 1, the authors proceed to elucidate the book’s themes in chapter 2: “Basic Concepts and Approaches.” In with pdfFactory ...